Antimicrobial management of Tropheryma whipplei endocarditis: the Spanish Collaboration on Endocarditis (GAMES) experience. (20th February 2019) - García-Álvarez, Lara; Sanz, M Mercedes; Marín, Mercedes; Fariñas, M Carmen; Montejo, Miguel; Goikoetxea, Josune; Rodríguez García, Raquel; de Alarcón, Arístides; Almela, Manuel; Fernández-Hidalgo, Nuria; Alonso Socas, M Mar; Goenaga, Miguel A; et al.
Abstract: Objectives: Tropheryma whipplei has been detected in 3.5% of the blood culture-negative cases of endocarditis in Spain. Experience in the management of T. whipplei endocarditis is limited. Here we report the long-term outcome of the treatment of previously reported patients who were diagnosed with infective endocarditis (IE) caused by T. whipplei from the Spanish Collaboration on Endocarditis-Grupo de Apoyo al Manejo de la Endocarditis Infecciosa en España (GAMES) and discuss potential options for antimicrobial therapy for IE caused by T. whipplei . Patients and methods: Seventeen patients with T. whipplei endocarditis were recruited between 2008 and 2014 in 25 Spanish hospitals. Patients were classified according to the therapeutic regimen: ceftriaxone and trimethoprim/sulfamethoxazole, doxycycline + hydroxychloroquine and other treatment options. Results: Follow-up data were obtained from 14 patients. The median follow-up was 46.5 months. All patients completed the antibiotic treatment prescribed, with a median duration of 13 months. Six patients were treated with ceftriaxone and trimethoprim/sulfamethoxazole (median duration 13 months), four with doxycycline + hydroxychloroquine (median duration 13.8 months) and four with other treatment options (median duration 22.3 months). The follow-up after the end of the treatments was between 5 and 84 months (median 24 months). Conclusions: All treatment lines were effective and well tolerated. Therapeutic failures were not detected during the treatment. None of the patients died or experienced a relapse during the follow-up. Only six patients received antibiotic treatment in accordance with guidelines. These data suggest that shorter antimicrobial treatments could be effective.